The Development of Homosexuality in the Modern Age from a Hadith Perspective - Insan Akbar; Fadhilah Is (AJIS: Academic Journal of Islamic Studies, 2024)
The purpose of this article is to explore the phenomenon of homosexuality in the contemporary world from the perspective of the prophetic traditions (Hadith) and to determine how Islamic teachings address the changing perception of sexuality. Through a qualitative thematic content analysis, this paper investigates hadiths of sexual behavior, including prophylactic moral norms and guardians of social ethics. Materials and methods: Data were extracted from six abridged versions of the canonical hadith collections. Using an approach that combines contextuality and normativity guided the analysis of Hadith in the light of the modern social context. The results suggest that the Hadith tradition maintains the heterosexual model as a normative ideal, providing moral advice to discourage deviant (including same-sex) practices through spiritual and legally-based dissuasive sanctions. This research demonstrates that prophetic preaching emphasizes legal prohibitions and promotes a proactive moral cultivation of acts as a preventative framework. The study's practical impact is offering reference material to those in Islamic education (teachers), preaching, and policy-making circles on how to critically and constructively respond to the problem of homosexuality that combines moral rigor with spiritual direction. What makes this book unique is its unified perspective that references both classical religious literature and modern social practices, thereby allowing for a comprehensive and sophisticated view of the function of Hadith in combating modern moral issues.